Upaya Meningkatkan Perkembangan Sosial Emosional (Kesadaran Diri) Melalui Metode Demonstrasi Pada Anak Usia 4-5 Tahun di PAUD Ibnu Abbas Kabupaten Cianjur - Sukmawati, Tena (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This research is motivated by the social-emotional ability (self-awareness) of 4-5 year old children in PAUD Ibnu Abbas, Cianjur Regency, which is still relatively low because in the learning process it is still rare to use innovative methods. So that the demonstration method applied is expected to be able to improve children's social-emotional skills (self-awareness). This research is a type of Classroom Action Research (PTK) in increasing children's self-awareness behavior through a routine habituation method in the Ibnu Abbas PAUD Institution Unit, Cianjur district, which aims to obtain changes in student behavior in increasing students' independence during learning at school. The research design used is the Kemmis and Mc. Taggart model design which contains four steps in one cycle including planning, implementation, observation and reflection. This research was carried out for six months with the research subject, namely half of the number of children aged 4-5 years at PAUD Ibnu Abbas, Cianjur Regency, namely 6 people. The data collection techniques in this study use observation and documentation with the data analysis techniques used, namely descriptive, qualitative, and quantitative. The results of this study show that learning with the application of the demonstration method in learning can improve children's social-emotional skills (self-awareness), this is evidenced by the improvement in children's abilities seen in the observation guidelines from before the action to the first cycle, namely before the action/pre-cycle got a result of 33.3% and the first cycle achieved a result of 66.7%. Then in the second cycle it achieved a result of 99%, where this final result has exceeded the research target which targets 90% success from action.